2014
DOI: 10.1155/2014/368215
|View full text |Cite
|
Sign up to set email alerts
|

“Sometimes It’s Difficult to Have a Normal Life”: Results from a Qualitative Study Exploring Caregiver Burden in Schizophrenia

Abstract: Objectives. As a disease typified by early onset and chronic disease course, caring for a person with schizophrenia may have a significant impact on caregivers' lives. This study aimed to investigate the subjective experiences of caregivers of people with schizophrenia as a means of understanding “caregiver burden” in this population. Methods. Face-to-face qualitative interviews were conducted with a diverse sample of 19 US-English speaking caregivers of people with schizophrenia (who were at least moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
67
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 65 publications
14
67
1
4
Order By: Relevance
“…However, similar to this study, Gater et al's [28] qualitative study showed that patients were dependent on caregivers for support. This burden is likely to impact negatively on the quality of life and may include physical and emotional health as well as psychological and social well-being of the carer [16].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, similar to this study, Gater et al's [28] qualitative study showed that patients were dependent on caregivers for support. This burden is likely to impact negatively on the quality of life and may include physical and emotional health as well as psychological and social well-being of the carer [16].…”
Section: Discussionsupporting
confidence: 81%
“…Awad and Voruganti [18] point to cultural factors that may in part play a role in the expression of caregiver burden and cited that Caucasians compared to African-descent Americans report higher levels of caregiver burden and have an attitude of rejection toward the patients. Gater et al's [28] qualitative study showed that due to a strong focus on faith and religion, the concept of caregiver ''burden'' was less [18]. It is possible therefore that the community mental health intervention for treatment in Jamaica has a positive impact on mental health stability, thereby decreasing the burden of caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…Negative consequences were described as “caregiver burden” more than half a century ago [8]. Given their impact on both caregivers and patients, the interest in understanding and managing caregiver burden has grown exponentially, not only in schizophrenia [9] but also in all other chronic health conditions [10]. …”
Section: Introductionmentioning
confidence: 99%
“…16 Kronik ruhsal bozukluğu olan bireylerin bakım verenlerinin yer aldığı çalışmalarda, bakım verenlerde öfke gösterilmiş ve bakım verenler bu öfkenin nedeninin hastaların davranışları olduğunu belirtmiş-lerdir. 17,18 Başka bir çalışmada, şizofreni hastalarının bakım verenlerindeki öfkenin nedenlerinin, bakım verenlerin aile içindeki rolleri ve şizofreni hastalarının tedavi süreçlerindeki maddi sorunlar olabileceği öne sürülmüştür. 3,19 Bu veriler ışığında şizofreni hastaları ile bakım verenleri arasındaki ilişkiyi sosyal anksiyete, saldırganlık ve bağlanma stilinin etkileyebileceğini düşünmekteyiz.…”
Section: Introductionunclassified